Penyuluhan Pemanfaatan Tanaman Obat Berkhasiat pada Budidaya Tanaman Green House di Kampung Langkob, Desa Majalaya, Cianjur, Jawa Barat - Ernie Halimatushadyah; Agnes Yuliana (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Counseling on the use of efficacious medicinal plants in the cultivation of greenhouse plants is one of the community service programs aimed at improving the health status of the people of Majalaya Village, especially the people of Langkob Village. This community service is expected to provide an understanding of the community benefits of various nutritious medicinal plants around. This activity was carried out by direct delivery method with a presentation of material related to the use of efficacious medicinal plants. The results achieved in this activity were an increase in public knowledge of the use of efficacious medicinal plants and understanding related to smart greenhouses as evidenced through statistical tests on the pre-test and post-test which were answered by the community in this series of activities. The statistical test resulted in a p-value <0.05, namely 0.013, which means that there was a significant difference when before the material was delivered and the material was delivered